2018
DOI: 10.1093/her/cyy032
|View full text |Cite
|
Sign up to set email alerts
|

A review of the impact of physical activity mass media campaigns on low compared to high socioeconomic groups

Abstract: Physical inactivity is a major contributor to non-communicable disease and people of low socioeconomic status (SES) are more likely to be insufficiently active. Physical activity mass media campaigns aim to increase physical activity participation, but little is known about their impact on low SES groups. We reviewed the published literature from 1990 to June 2016 to identify reports of physical activity mass media campaigns. We documented evaluation/study design, target population, campaign outcomes assessed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…We also examined whether different indicators of social disadvantage moderated the effect of campaign exposure on two indicators of PA: meeting PA recommendations and trying new PAs. Consistent with the systematic review of Thomas et al (2018 ) findings of the present study revealed no clear evidence for communication inequalities associated with the WIXX campaign on behavioral outcomes. More importantly and despite the fact that exposure varied according to some indicators, we observed that the campaign led to more favorable behavioral outcomes among girls belonging to minority groups and living in areas characterized by higher levels of social deprivation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also examined whether different indicators of social disadvantage moderated the effect of campaign exposure on two indicators of PA: meeting PA recommendations and trying new PAs. Consistent with the systematic review of Thomas et al (2018 ) findings of the present study revealed no clear evidence for communication inequalities associated with the WIXX campaign on behavioral outcomes. More importantly and despite the fact that exposure varied according to some indicators, we observed that the campaign led to more favorable behavioral outcomes among girls belonging to minority groups and living in areas characterized by higher levels of social deprivation.…”
Section: Discussionsupporting
confidence: 89%
“…( Niederdeppe et al, 2008 , Bala et al, 2017 , McGill et al, 2015 ). Regarding PA communication campaigns, Thomas et al (2018 ) recently concluded that no clear communication inequalities would be likely to occur from this type of intervention among adults. Nevertheless, some of the campaigns included in this review showed poorer campaign outcomes among socioeconomically disadvantaged groups.…”
Section: Introductionmentioning
confidence: 99%
“…A few reviews aimed specifically to assess the equity impact of mass-media interventions. 25 , 31 One of these observed that when campaigns focused specifically on low socioeconomic subgroups, they were generally more effective in reaching this group, 31 while the reach of broadly targeted was equal in high and low socioeconomic groups. 6 , 25 Outcomes of broad campaigns were not large enough to reduce socioeconomic inequalities.…”
Section: Resultsmentioning
confidence: 99%
“…However, the qualitative data from the studies included in this review highlight that, in general, children are aware of the multitude of short- and long-term benefits from physical activity. These differences could reflect an increased societal focus on health in which children are more frequently exposed to physical activity and health-related messages through mass media campaigns [ 49 ].…”
Section: Discussionmentioning
confidence: 99%